2021
DOI: 10.1037/pha0000361
|View full text |Cite
|
Sign up to set email alerts
|

Online personalized feedback intervention reduces cannabis-related problems among college students with high problem distress.

Abstract: Despite experiencing problems related to using cannabis, very few undergraduate cannabis users are interested in treatment for cannabis-related problems or benefit from cannabis-focused online personalized feedback interventions (PFIs). Thus, it may be important to determine whether individuals perceive their problems as distressing, as only those who are distressed by their problems may be motivated to change their cannabis use or benefit from cannabis-related interventions. The current study examined cannabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…For instance, one study using the monitoring the future data found that while 8.2% of young adults endorsed using alcohol to cope with the pandemic, this was nearly double (15.7%) for cannabis use, and that only cannabis use coping motives were associated with isolation experienced during the pandemic (Patrick et al, 2022). It is notable that certain SM groups were already engaging in higher rates of solitary cannabis use (Tucker et al, 2008) and cannabis coping motives (Walukevich-Dienst et al, 2019, 2021) compared to their non-SM peers before the pandemic. Certain SM groups also report higher rates of solitary cannabis use than solitary drinking (Dyar, Feinstein, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study using the monitoring the future data found that while 8.2% of young adults endorsed using alcohol to cope with the pandemic, this was nearly double (15.7%) for cannabis use, and that only cannabis use coping motives were associated with isolation experienced during the pandemic (Patrick et al, 2022). It is notable that certain SM groups were already engaging in higher rates of solitary cannabis use (Tucker et al, 2008) and cannabis coping motives (Walukevich-Dienst et al, 2019, 2021) compared to their non-SM peers before the pandemic. Certain SM groups also report higher rates of solitary cannabis use than solitary drinking (Dyar, Feinstein, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were from a sample of 268 undergraduates recruited for the parent intervention trial ( Morris & Buckner, 2023 ; Walukevich-Dienst et al, 2021 ; Walukevich-Dienst et al, 2019 ). For the parent study, eligible participants were current undergraduate students at Louisiana State University who reported past-month cannabis use and at least one cannabis-related problem in the past three months.…”
Section: Methodsmentioning
confidence: 99%
“…The present aims were tested through secondary data analyses from a study that developed and tested problem-focused personalized feedback (PFI) against brief personalized normative feedback (PNF; Morris & Buckner, 2023 ; Walukevich-Dienst et al, 2021 ; Walukevich-Dienst et al, 2019 ). Neither domains of risk nor baseline associations between risk domains and outcomes were examined as part of the parent study primary aims.…”
Section: The Current Studymentioning
confidence: 99%
“…For example, mandated treatment programs have been consistently shown to reduce alcohol (Carey et al, 2016) and cannabis use (Buckner et al, 2018) among students. Various studies have also demonstrated the effectiveness of non-mandated web- or computer-based as well as in-person interventions for reducing college students’ substance use (e.g., Cadigan et al, 2015; Walukevich-Dienst et al, 2020). The availability of effective interventions for reducing college student substance use further supports the need to understand intervention receptiveness among this population.…”
Section: Treatment Seeking Behaviorsmentioning
confidence: 99%